The effect of fintech M&As on short-term stock return in the context of macroeconomic environment - Elena Ochirova; Mikhail Miriakov (Financial Innovation)
Abstract Mergers and acquisitions (M&A) with financial technology (fintech) companies can be an effective way for firms to obtain new technologies and capabilities. However, the market reaction to fintech M&A announcements has received limited attention in the empirical academic literature. This study assesses the impact of fintech M&As on stock returns and examines whether macroeconomic variables influence the abnormal return of fintech M&As. Using event study analysis, we found that fintech M&A announcements generate a significant positive short-term abnormal return. Furthermore, we demonstrated that macroeconomic parameters, including Gross domestic product (GDP) growth, inflation rate, the share of services in GDP, and aggregate export growth, positively affect abnormal returns. In contrast, private investment, consumer spending, and an economy’s size negatively influence fintech M&As’ abnormal returns.